2017
DOI: 10.1002/2017gl075163
|View full text |Cite
|
Sign up to set email alerts
|

Stress‐ and Structure‐Induced Anisotropy in Southern California From Two Decades of Shear Wave Splitting Measurements

Abstract: We measure shear wave splitting (SWS) parameters (i.e., fast direction and delay time) using 330,000 local earthquakes recorded by more than 400 stations of the Southern California Seismic Network (1995–2014). The resulting 232,000 SWS measurements (90,000 high‐quality ones) provide a uniform and comprehensive database of local SWS measurements in Southern California. The fast directions at many stations are consistent with regional maximum compressional stress σHmax. However, several regions show clear deviat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
45
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 38 publications
7
45
2
Order By: Relevance
“…The resulting fast orientations of crustal anisotropy are in general agreement with those obtained by recent crustal anisotropy studies using RFs (e.g., Porter et al, ; Schulte‐Pelkum & Mahan, ), surface wave tomography (F. Lin et al, ), and splitting of shear waves from local earthquakes (e.g., Z. Li & Peng, ; Z. Yang et al, ). Areas close to major strike‐slip faults show NW‐SE oriented ϕ values, which are consistent with fault strike and can be attributed to fluid‐filled fractures in the upper crust associated with the numerous strike‐slip faults in the study area including the San Andreas Fault system (Crampin, ; Z. Li & Peng, ), and shear‐deformed schists in the lower crust (Porter et al, ; Schulte‐Pelkum & Mahan, ). Detailed discussions about crustal anisotropy in the study area can be found in several recent crustal anisotropy studies that have a much higher lateral resolution than what is used (1°) in this study (Z. Li & Peng, ; F. Lin et al, ; Porter et al, ; Schulte‐Pelkum & Mahan, ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The resulting fast orientations of crustal anisotropy are in general agreement with those obtained by recent crustal anisotropy studies using RFs (e.g., Porter et al, ; Schulte‐Pelkum & Mahan, ), surface wave tomography (F. Lin et al, ), and splitting of shear waves from local earthquakes (e.g., Z. Li & Peng, ; Z. Yang et al, ). Areas close to major strike‐slip faults show NW‐SE oriented ϕ values, which are consistent with fault strike and can be attributed to fluid‐filled fractures in the upper crust associated with the numerous strike‐slip faults in the study area including the San Andreas Fault system (Crampin, ; Z. Li & Peng, ), and shear‐deformed schists in the lower crust (Porter et al, ; Schulte‐Pelkum & Mahan, ). Detailed discussions about crustal anisotropy in the study area can be found in several recent crustal anisotropy studies that have a much higher lateral resolution than what is used (1°) in this study (Z. Li & Peng, ; F. Lin et al, ; Porter et al, ; Schulte‐Pelkum & Mahan, ).…”
Section: Discussionsupporting
confidence: 87%
“…Areas close to major strike‐slip faults show NW‐SE oriented ϕ values, which are consistent with fault strike and can be attributed to fluid‐filled fractures in the upper crust associated with the numerous strike‐slip faults in the study area including the San Andreas Fault system (Crampin, ; Z. Li & Peng, ), and shear‐deformed schists in the lower crust (Porter et al, ; Schulte‐Pelkum & Mahan, ). Detailed discussions about crustal anisotropy in the study area can be found in several recent crustal anisotropy studies that have a much higher lateral resolution than what is used (1°) in this study (Z. Li & Peng, ; F. Lin et al, ; Porter et al, ; Schulte‐Pelkum & Mahan, ).…”
Section: Discussionsupporting
confidence: 56%
“…This suggests that, particularly north of Hawkes Bay, the forearc is under a compressional stress regime, whereas the underlying Hikurangi slab is undergoing strike‐slip deformation. It is interesting to compare our results to a similar study from southern California (Li & Peng, ). Seismic anisotropy patterns from California appear to be predominantly controlled by crustal structures, such as faults.…”
Section: Discussionmentioning
confidence: 65%
“…Seismic anisotropy, the directional dependence of seismic wave speed, is an intrinsic property of the Earth's crust and can be measured by the detection of shear‐wave splitting (Illsley‐Kemp et al, ; Johnson et al, ; Li & Peng, ; Savage, ). Numerous studies have suggested that seismic anisotropy is caused by structural features such as faults (Boness & Zoback, ; Zinke & Zoback, ) and/or aligned melt pockets (Ando & Ishikawa, ; Bastow et al, ; Dunn et al, ; Keir et al, ), where the shear‐wave fast orientation is parallel to the trend of structural features.…”
Section: Introductionmentioning
confidence: 99%
“…These values are approximately perpendicular to the regional S hmin (Figure ) inferred from the World Stress Map (http.//http://www.world-stress-map.org; Heidbach et al, ) and from the Italian stress map (Mariucci & Montone, ). The orthogonality between the fast direction and the S hmin stress indicator is widely observed worldwide, that is, in the Shillong‐Mikir Plateau of Northeast India (Bora et al, ), in the Kyushu area in Japan (Savage et al, ), and in Southern California (Li & Peng, ). Moreover, previous studies on seismic anisotropy focused on the Italian peninsula invoke the EDA model to explain the observed pattern of fast axes (Baccheschi et al, ; Guerri et al, ; Pastori et al, , , ; Piccinini et al, ).…”
Section: Discussionmentioning
confidence: 99%